The Poppy Fields : a novel - Erlick, Nikki (William Morrow, an imprint of HarperCollinsPublishers, 2025)
"Welcome to the Poppy Fields, where there's hope for even the most battered hearts to heal. Here, in a remote stretch of the California desert, lies an experimental and controversial treatment center that allows those suffering from the heartache of loss to sleep through their pain... and keep on sleeping. After patients awaken from this prolonged state of slumber, they will finally be healed. But only if they're willing to accept the potential shadowy side effects. On a journey to this mystical destination are four very different strangers and one little dog: Ava, a book illustrator; Ray, a fireman; Sasha, an occupational therapist; Sky, a free spirit; and a friendly pup named PJ. As they attempt to make their way from the Midwest all the way to the Poppy Fields--where they hope to find Ellis, its brilliant, enigmatic founder--each of their past secrets and mysterious motivations threaten to derail their voyage."--